Recent Modifications and Validation of QuEChERS-dSPE Coupled to LC–MS and GC–MS Instruments for Determination of Pesticide/Agrochemical Residues in Fruits and Vegetables: Review - Lawal, Abubakar; Wong, Richard Chee Seng; Tan, Guan Huat; Abdulra'uf, Lukman Bola; Alsharif, Ali Mohamed Ali (Oxford University Press, 2018)
Fruits and vegetables constitute a major type of food consumed daily apart from whole grains. Unfortunately, the residual deposits of pesticides in these products are becoming a major health concern for human consumption. Consequently, the outcome of the long-term accumulation of pesticide residues has posed many health issues to both humans and animals in the environment. However, the residues have previously been determined using conventionally known techniques, which include liquid-liquid extraction, solid-phase extraction (SPE) and the recently used liquidphase microextraction techniques. Despite the positive technological effects of these methods, their limitations include; time-consuming, operational difficulty, use of toxic organic solvents, low selective property and expensive extraction setups, with shorter lifespan of instrumental performances. Thus, the potential and maximum use of these methods for pesticides residue determination has resulted in the urgent need for better techniques that will overcome the highlighted drawbacks. Alternatively, attention has been drawn recently towards the use of quick, easy, cheap, effective, rugged and safe technique (QuEChERS) coupled with dispersive solid-phase extraction (dSPE) to overcome the setback challenges experienced by the previous technologies. Conclusively, the reviewed QuEChERS-dSPE techniques and the recent cleanup modifications justifiably prove to be reliable for routine determination and monitoring the concentration levels of pesticide residues using advanced instruments such as high-performance liquid chromatography, liquid chromatography-mass spectrometry and gas chromatography-mass spectrometry.